A comparison of clinical outcomes among people living with HIV of different age groups attending queen Elizabeth central hospital outpatient ART Clinic in Malawi - Chakakala-Chaziya, Jessica; Patson, Noel; Samuel, Vincent; Mbotwa, John; Buonsenso, Danilo; Chisale, Master; Phiri, Eddie; O’Hare, Bernadette (Frontiers in Medicine, 2023)
Introduction: Adherence to on Antiretroviral Treatment (ART) in children and adolescents living with HIV in low-resource settings is not extensively studied on in large cohort studies comparing including both adults and pediatric patients. We compared rates of virological suppression, adherence and , defaultingretention to care and mortality amongof children, adolescents and adults attending a family ART clinic at Queen Elizabeth Central Hospital; a tertiary hospital situated in the southern region of Malawi. Methods: The study was longitudinal and made use of routinely collected data for all 27,229 clinic attendees. Clinical information obtained at routine clinical reviews visits entered electronically since 2008 was extracted in February 2017. This data was used to ascertain differences across the different age groups.; Llogistic regression and Cox regression models were fitted to compare rates of Virological Suppression (VS), adherence, ; and and defaulting and mortality respectively. Results: Adults were more likely than other age groups to achieve VS. Younger and olderOlder and younger adolescentsteens(ages 10-14 years and 15-19 years respectively) were less likely to achieve VS compared to adults in the final model AOR 0.4 (0.2-0.9, 95% CI) and AOR 0.2 (0.1-0.4, 95% CI) respectively. Young childrenchildren (ages 0-4years) , older children(ages 5-9years) and younger adolescents were less adherent to ART compared to adults AOR 0.1(0.1-0.2, 95% CI), AOR 0.2 (0.1-0.3, 95% CI) and AOR 0.4 (0.3-0.5, 95% CI) respectively. There were no differences in death rates across the different ages, however Yyoung adults and younger children had an increased likelihood of defaulting compared to adults. Conclusions: Poorer performance on ART of children and adolescents highlights unaddressed challenges to adherence. Ongoing research to explore these potential barriers and possible interventions needs to be carried out. The adherence assessment methods used and strategies for improving it among children and adolescents need to be revised at the clinic.